Employer's perceptions and Higher Education Institutions initiatives towards UAE Graduate Employability - HASSOCK, LEISA JANE (2019)
The purpose of this study investigates the employability of UAE graduates by i) confirming what initiatives Higher Education Institutions are currently implementing to improve UAE graduate employability, ii) determining what initiatives Employers require Higher Education Institutions to implement to improve their employability, iii) identifying the main influences for Employers when deciding to employ UAE graduates. The UAE government is focused on developing a knowledge economy as the use of fossil fuels become redundant. The study used a qualitative approach utilizing in-depth interviews and focus groups with Employers across all UAE industry sectors as well as Higher Education Institutions to identify employer perceptions concerning UAE graduate employment and work readiness. The findings required graduates to develop soft skills, particularly communication skills together with a stronger work ethic and a focus on lifelong learning. A mixed-method approach was commenced however the quantitative data portion was abandoned when data from questionnaires became limited. Qualitative data however provided valuable in-depth and constructive responses. The findings from this study support the development of curriculum planning and strategic decision making as well as strategic economic and workforce planning. The study identifies employers’ perceptions of UAE graduate’s employability and the current education processes Higher Education Institutions (HEIs) are taking towards work readiness for graduate employability.